The Ability To Analyze English Vowels In Films - Alzuhda, Najwa; Pardamean; Lubis , Yani (Jurnal Pendidikan Rafflesia, 2023)
The ability to analyze English vowels in films is an important skill in understanding English pronunciation and intonation used in audiovisual contexts. In this essay, we will explore the importance of being able to analyze English vowels in a film context, and how this ability can enrich our understanding and appreciation of English in cinematic settings. The background of this research includes the growing popularity of film in teaching English as an effective means of improving language skills. Film provides a unique opportunity to expand vocabulary, deepen cultural understanding, and hone listening skills. However, in order to maximize this benefit, it is important for us to be able to analyze and understand the pronunciation used by the actors in the film.The formulation of the problem that arises is how the ability to analyze English vowels can affect our understanding and appreciation of English in the context of film. The purpose of this study is to explore various techniques and strategies that can be used in analyzing English vowels in films, and to see how our understanding and appreciation of English in a cinematic context can be improved through this ability.The discussion in this essay will include an explanation of the importance of analyzing English vowels in films, including how using the right vowels can enrich the dialogue and express the emotions of the characters. We will also discuss various techniques and strategies that can be used to analyze English vowels, such as the use of IPA (International Phonetic Alphabet) and the acoustic approach.Through analyzing English vowels in films, we can develop a better understanding of the variations and characteristics of vowels in English, as well as improve our listening and speaking abilities. This will have a positive impact on our ability to communicate in English and broaden our cultural horizons.In conclusion, the ability to analyze English vowels in films is an important aspect in understanding and appreciating English in a cinematic context. By using the right techniques and strategies, we can improve our understanding and language skills through careful vocal analysis. Therefore, it is highly recommended to develop this ability as part of learning English, especially in the context of teaching films.